Clusters and their driving forces - lessons learned from the CNCB project - Jarjabka, Ákos (Marketing & Menedzsment, 2019)
AIMS OF THE STUDY The aims of the article are to deal with the global role of clusters, to examine certain major features of their development, to define the driving forces behind their establishment and success and to analyse the results of an empirical research project. By this, it is hoped to make some contribution to the general results of research into the role of clusters in improving the performance of the economy. METHODOLOGY The study analyses the Cluster and Network Cooperation for Business Success in Central Europe (CNCB) project - an exercise focusing on three crucial areas which help to establish and sustain the development of clusters (HR Development in clusters, the optimisation of cluster processing and the internationalisation of clusters). To present the results of this empirical research, statistical methods, such as descriptive statistics and one-variable analytical methods, pair comparison such as cross-tables were used - together with regional, sectoral and size- related comparisons, factor-, variance and scoring analysis. THE MOST SIGNIFICANT FINDINGS The analyses show that significant relations exist only in internally driven, optimised clusters: there are none between the global composite indices (measuring economic development and competitiveness) and the data set examined. Negative correlations can be interpreted as problems within the system of supporting clusters. PRACTICAL SUGGESTIONS The findings of the study should be of interest to all those involved in establishing and developing clusters, in their direct funding or in applications for appropriate resources. The use of development resources and funds is only effective if the clusters are motivated not only to meet the bureaucratic requirements of the applications, but also to build and maintain an ecosystem based on serious cooperation and where the use of funds is monitored and reflected by business performance indicators.